A review of calcined clays and ceramic wastes as sources for alkali-activated materials. Issue 5 (2nd September 2020) - Rakhimova, Nailia R.
ABSTRACT: Expanding and optimising the raw materials base in accordance with increasing ecological and technical requirements is one of the determining factors of a promising future for the constantly evolving alkali-activated materials (AAMs). Because of the development of the chemistry of the inorganic materials, the range of potentially suitable aluminosilicates has changed and expanded continuously throughout the history of AAMs. Relatively recently, efforts to find more types of adequate, alternative aluminosilicate sources, in addition to conventional granulated blast furnace slag, fly ash, and metakaolin, have led to extensive studies that have substantially increased understanding around the suitability of various natural sources and wastes for production of AAMs. In recent decades, calcined clays and ceramic wastes have become significant as an alumino-silicate sources for AAMs. Extensive research forms the theoretical and practical bases for the application of calcined clays, which are diverse in composition and structure, for effective cement production. This paper reviews recent developments in the field of alkali-activated cement-based systems using calcined clays containing different amounts of 1:1 and/or 2:1 type clay and secondary minerals, and ceramic wastes, including their suitability aspects, processing features, chemical reactivities, controlling factors, potential for application.